Innovations in Electronics and Communication Engineering Proceedings of the 7th ICIECE 2018 - Saini, H. S.; Singh, R. K.; Kumar, Girish; Rather, G.M.; Santhi, K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book gathers selected papers presented at the 7th International Conference on Innovations in Electronics and Communication Engineering, held at Guru Nanak Institutions in Hyderabad, India. It highlights contributions by researchers, technocrats and experts regarding the latest technologies in electronic and communication engineering, and addresses various aspects of communication engineering, including signal processing, VLSI design, embedded systems, wireless communications, and electronics and communications in general. Covering cutting-edge technologies, the book offers a valuable resource, especially for young researchers. .
Detection and Classification of Exudates and Non-Exudates in Retinal Images -- A Study on Smart Electronics Voting Machine Using Face Recognition and Aadhar Verification with IOT -- Exhaustive Analysis of Image Enhancement Using Point to Point Transformation -- Quantized Local Trio Patterns for Multimedia Image Retrieval System -- Multiple Color Channel Local Extrema Patterns for Image Retrieval -- Posture Monitoring and Back Pain Relief Using ATmega328, Android and Unity -- Performance Analysis of Nanoparticles in Healthcare and Biomedical Applications -- Preliminary Investigation of Generation of US based GPS Signal -- A Study On Neutron Star Interior Composition Explorer Contributions to Springer Proceedings -- Estimation of Face Pose Orientation Using Model Based Approach -- Accurate Classification of Cancer in Mammogram Images. .
Keywords: Telecommunication; Signal processing; Electric power production; Communications Engineering, Networks; Signal, Speech and Image Processing; Electrical Power Engineering